Quality Perception: Navigating Satisfaction and Review Credibility Pathways - Putu Tasya Villia Dewi; Nilna Muna (Eduvest - Journal of Universal Studies, 2024)
This study investigates the impact of product quality on customer perceived value, cus-tomer satisfaction, and information review credibility, alongside the mediating role of cus-tomer satisfaction and information review credibility. The research employs the Infor-mation Adoption Model (IAM) to explore how these variables influence customer prefer-ences in the e-commerce sector, focusing on Somethinc skincare products in Denpasar City. Data from 126 respondents were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Results show that product quality positively affects customer perceived value, customer satisfaction, and information review credibility. Information review credibility effectively mediates the relationship between product quality and cus-tomer perceived value, while customer satisfaction does not. These findings provide theo-retical contributions to IAM and practical insights for businesses to enhance customer trust and value perception through improved product quality and credible information dissemination.